2006
DOI: 10.1002/pros.20450
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and anti-androgen treatment modulates androgen receptor activity and DJ-1 stability

Abstract: Stabilization of AR and its co-regulators in the absence of androgen may partially account for anti-androgen withdrawal syndrome and potentially contribute to the development of hormone refractory PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Previously, we showed that antiandrogen treatment could stimulate AR-regulated signaling in a subpopulation of HPE cells cultured from prostate biopsy specimens (11). Proteomic analysis identified DJ-1 as a protein whose expression was up-regulated by both androgen and antiandrogen treatment and that this increase was due to DJ-1 and AR protein stability.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously, we showed that antiandrogen treatment could stimulate AR-regulated signaling in a subpopulation of HPE cells cultured from prostate biopsy specimens (11). Proteomic analysis identified DJ-1 as a protein whose expression was up-regulated by both androgen and antiandrogen treatment and that this increase was due to DJ-1 and AR protein stability.…”
Section: Introductionmentioning
confidence: 92%
“…Western blot analysis confirmed this result, showing that DJ-1 and AR protein levels increased following treatment with dihydrotestosterone (DHT), the synthetic androgen R1881, or the antiandrogen hydroxy-flutamide (OH-flutamide) in LNCaP cells. Blocking protein synthesis with cycloheximide revealed that the increase in DJ-1 was due to increased protein stability (11). This indicated that DJ-1 and AR expression was regulated by both androgens and antiandrogen therapy and may be involved in AIPC.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The LNCaP human prostate cancer cell line was obtained from American type culture collection and was cultured as described by Pitk€ anen-Arsiola et al 54 LNCaP cells were grown in 10 cm plates and when they are 80% confluence, the cells are stained with the green fluorescent chloromethyl derivatives of fluorescein diacetate (CMFDA). The cells were stained following manufacturer's protocol (MP02925, Life Technology, Inc.).…”
Section: Protocolsmentioning
confidence: 99%
“…A few investigators have analyzed mechanisms underlying AWS other than mutations of AR gene (16)(17)(18). Pitkänen-Arsiola et al reported that stabilization of AR and its co-regulator, DJ-1, in the absence of androgen may partially account for AWS (16).…”
Section: Discussionmentioning
confidence: 99%